Determinates of Formation and Development of German Newspaper-Publicistic Style in 19th Century - A. V. Kokova (Научный диалог)
The article considers theoretical problems of the language functioning on the example of formation and development of the German newspaper-publicistic style. Thus, the author presents the development of a system for the regulation of style and language capacity of the means of expression, which is based on two types of heterogeneous principles, strictly deterministic, on the one hand, and stochastic, based on probability criteria, on the other hand. The research urgency is caused by the need to establish specific determinates of stylistic system development, giving objective, summarizing basis for a theoretical understanding of disparate empirical facts. It is established that general dialectic determinates of development of stylistic language system are causality and appropriateness. Specific determinates that determine the functional specificity of the studied style - newspaper-publicistic style of the German language at the final stage of its formation in the 19th century: the stylistic principles of appropriateness, clarity, consistency and ostensiveness. It is proved that the dominant way of thematic deployment of the publicistic text in the German language is the argumentative method based on the method of practical reasoning. Certain language features of common style principles are considered as stochastic (probable, possible).